Expiry and its application in the police disciplinary administrative procedure - Salas Vásquez, Pedro Pablo (2022)
In the present article, the figure of administrative expiration is developed from the approach of police disciplinary administrative procedures. In that matter, the author approaches the subject from the analysis of Law No. 27444, Law of General Administrative Procedure, and the rules that shape the disciplinary regime of the National Peruvian Police. This work constitutes an important effort that consolidates the policys that must be followed by both the operators and the administrators of the Police Disciplinary System for the proper calculation of the expiration period.